Unveiling Putative Functions of Burkholderia pseudomallei K96243 Hypothetical Proteins Via High-Throughput Characterization of Structural Similarities - Syed Abuthakir Mohamed Husain; Su Datt Lam; Mohd Firdaus-Raih; Sheila Nathan; Nor Azlan Nor Muhammad; Chyan Leong Ng (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Integrative multi-omics and biochemical validation reveal phenol-to-polyhydroxybutyrate conversion in a palm oil mill effluent microbiome - Izzati Sabri; Siti Suhailah Sharuddin; Mohd Zulkhairi Mohd Yusoff; Nor Azlan Nor Muhammad; Li Sim Ho; Toshinari Maeda; Norhayati Ramli (Journal of Water Process Engineering, 2026)

Network perspectives on transcriptomic datasets to understand shrimp response mechanisms to environmental and pathogenic stresses: a review - Noorul Darlina Edlin Abd Rahim; Nor Azlan Nor Muhammad; Khor Waiho; Sarahani Harun; Rabiatul-Adawiah Zainal-Abidin; Min Pau Tan; Yeong Yik Sung; Zeti-Azura Mohamed-Hussein; Nor Afiqah-Aleng (Aquaculture International, 2026)

In Silico Identification of MYB Transcription Factors Involved in Mangosteen Anthocyanin and Xanthone Production - Ching-Ching Wee; Masanori Arita; Intan Azlinda Ramlee; Nor Azlan Nor Muhammad; Vijay Kumar Subbiah; Hoe-Han Goh (Tropical Plant Biology, 2026)

Physicochemical characterization, lipid-modulating effects, and proteomic insights of Malaysian Sacha Inchi (Plukenetia volubilis L.) seed oil in HepG2 cells - Mariam Fardush; Norsyahida Mohd Fauzi; Ho Wen Yan; Armania Nurdin; Ibrahim Jantan; Nor Azlan bin Nor Muhammad; Siti Nurlisa Hazim; Sarmila Hanim binti Mustafa; Kimberlyn Feguro (Food Bioscience, 2025)

Farnesol dehydrogenase from Metisa plana (Lepidoptera: Psychidae): Biochemical characterization, in silico analysis and inhibitors discovery - Anis Nadyra Zifruddin; Ahmad Faris Seman Kamarulzaman; Nor Azlan Nor Muhammad; Kok Wai Lam; Cik Mohd Rizuan Zainal Abidin; Maizom Hassan (Pesticide Biochemistry and Physiology, 2025)

In silico prediction of effector proteins in oil palm pest, Metisa plana - Mohamad Ariff Mohamad Yussoff; Maizom Hassan; Norfarhan Mohd-Assaad; Nurul Wahida Othman; Suhaila Sulaiman; Cik Mohd Rizuan Zainal Abidin; Nor Azlan Nor Muhammad (Journal of Asia-Pacific Entomology, 2024)

Insights of the Rhynchophorus ferrugineus chemosensory system towards controlling its palm infestation problem: Progress from Omics research and technologies - Rajeswari Kalepu; Maizom Hassan; Norfarhan Mohd Assa’ad; Azzmer Azzar Abdul Hamid; Nor Azlan Nor Muhammad (International Journal of Tropical Insect Science, 2024)

Current progress on the computational methods for prediction of host-pathogen protein-protein interaction in the Ganoderma boninense-oil palm pathosystem - Mohamad Hazwan Fikri Khairi; Nor Azlan Nor Muhammad; Hamidun Bunawan; Kauthar Mohd Daud; Suhaila Sulaiman; Zeti-Azura Mohamed-Hussein; Mui-Yun Wong; Ahmad Bazli Ramzi (Physiological and Molecular Plant Pathology, 2024)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Nor Hashikin Katni; Amirul Faiz Mohd Azmi; Maizah Mohd Abdullah; Mohd Uzair Rusli; Zunita Zakaria; Tengku Rinalfi Putra Tengku Azizan; Azlan Che’ Amat; Mohd Zamri Saad; Ina Salwany Md. Yasin; Muhammad Farhan Nazarudin; Hasliza Abu Hassim (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences ( p >0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.